Efek Penambahan Variasi Larutan Ion Ag+ dalam Pembuatan Kertas Antibakteri Berbasis Pulp Selulosa dari Kulit Kopi - Sutiarno sutiarno; Muhammad Jundy Al Faruq; Fakhri Izdihar Prayitno Putra; Chayyara Igda Prameswari; Azizah Azmi Nurohmah; Kinasih Cahyono; Fatkhur Rohman; Gurum Ahmad Pauzi (Jurnal Teori dan Aplikasi Fisika, 2024)
Coffee skin contains cellulose, reaching 49%, so the material has the potential to be used as a substitute for the main material of wood in the paper industry. To obtain pure cellulose coffee skin, the lignin delignification process was carried out using 15% NaOH. Then, it was bleached by adding 10% H2O2. The bleached precipitate was washed to a neutral pH and dried. Coffe Skin Cellulose mixed with sago starch as an adhesive was weighed in a ratio of 1:3. To improve the quality of the paper, the material was mixed with a solution of Ag+ ions in a ratio of 2:1 to form pulp.The process of making an Ag+ ion solution involves forming two AgBr plates into electrodes with a distance of 1 cm in 400 ml of aquades. The electrolysis stage used V = 25 volts by checking the concentration of the solution using a TDS meter every 10 minutes. Then, the electrolysis solution underwent four variations in concentration, namely 18, 21, 24, and 27 ppm. Next, the paper is printed and dried using sunlight. This study reviewed the effect of variations in the concentration of Ag+ ion solutions coated on paper on functional groups and antibacterial properties. The results of UV-Vis analysis revealed Ag+ ions in the wavelength range of 400–439 nm. As the concentration increases, so does the absorbance peak. Then, functional group analysis indicated a shift in the absorption band peak of the N-H bending group due to reduced binding by Ag+ ions. In the results of bacterial testing, all samples had clear zone values, with an average diameter of Bacillus sp. 3.7 mm and Escherichia coli 4.65 mm. The ability of paper samples to inhibit bacteria was still weak. Keywords: Paper, Ag+ ions, Cellulose, coffee skin, antibacterial.